Seolsongdo (설송도) by Yi Insang (이 인상, 1710–1760) as an embodiment of the symbolic interpretation of the pine tree image in Korean fine art - Yu. I. Gutareva (Шаги)
The article analyses the scroll Seolsongdo (설송도) of Yi Insang (이인상), an outstanding Korean painter of the late Joseon era. The scroll depicts snow-covered pines, an image through which the artist managed to most clearly embody the complex syncretic set of ideas inherent in Korean culture, and to display the inner spiritual state. The author makes an attempt to use the example of Yi Insang’s work to reveal the peculiarities of the artistic image of the pine tree, to identify the symbolic meaning and explain the ideological component of the image, defining its place and significance in Korean fine art as an important element of the visual system, necessary for the preservation of the cultural tradition and national character. The main conclusion of the article is that the image of the pine tree, being one of the key images in Korean fine art, characterized by spiritual content and depth of philosophical and aesthetic ideas of the Joseon era, has vitality and does not lose relevance in the works of Korean artists of today, embodying elements of a new conceptual perception of the national cultural code, integrating and enriching it with new forms, modern technology and various materials.